Political and cultural representations of Muslims Islam in the plural - Flood, Christopher (Leiden ; Boston : Brill, 2012)
Relations between Muslims and non-Muslims have received unprecedented attention since 9/11. In many predominantly non-Muslim countries intense debates have focused on international relations with Muslim-majority states, but dilemmas of national policy and practice in incorporating domestic Muslim minorities have also provoked heated argument. Meanwhile, within predominantly Muslim societies, and within Muslim diasporas, relationships with non-Muslims have posed pressing questions about compatibility, antagonism or adaptation of beliefs, identities and customs. The essays forming this multidisciplinary collection analyse concerns arising from clashing perceptions of Muslims in the political and cultural spheres: the majority of chapters deal with non-Muslim representations of Muslims, but several chapters reverse the perspective by examining Muslims' own understandings of their relationships with non-Muslim societies.0.
Includes bibliographical references and index.
Print version record.
Keywords: Muslims -- Non-Islamic countries; Muslims -- Public opinion; Islam and politics; Islam -- 21st century; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Islam; Islam and politics; Muslims; Muslims -- Public opinion; Non-Islamic countries; Muslimer; Muslimer -- attityder till; Islam och politik; Islam -- 21st century; Islam and politics; Muslims -- Non-Muslim countries; Muslims -- Public opinion; 2000 - 2099; Electronic books; Electronic books